Origins and history of global and Polish clinical pharmacy - Adamiszak, Arkadiusz; Adamiszak, Sylwia (Family Medicine & Primary Care Review, 2024)
The history of global clinical pharmacy can be traced back to the second half of the 20th century. The initiators of the first efforts to disseminate the practice of clinical pharmacists were American pharmacists and American research centers. Not much later, the promotion of clinical pharmacy began on the Old Continent, more specifically in the United Kingdom. To this day the United States and the United Kingdom are role models for clinical pharmacists around the world. Our review aimed to present historical milestones and the current potential of clinical pharmacy services. We investigated articles catalogued in the PubMed database and searched for information on pharmaceutical universities’ and governments’ websites. Based on previous experiences in the USA and UK, pharmacists in other countries are gradually trying to implement their solutions to introduce clinical pharmacy services into the daily healthcare routine. This is facilitated by the increasing need to individualize treatment therapies tailored to the patient’s needs and the overload on health systems which are becoming some of the main arguments for including pharmacists in multidisciplinary teams. Clinical pharmacists’ high aspirations, as well as determination, coupled with the acceptance of the medical community and government, promise to be of rapidly discernible benefit to patients, medical staff and government finances alike. The current situation equally affects Polish clinical pharmacists, who wait for legal conditions and initial acceptance by the clinical community, enabling them to work in hospital units. This raises a question: If not now, then when?